M. P. Leganés Moya y F. G. Hernández Muñoz, Demosthenis in Midiam, Universidad de León, 2008. 183 pp. ISBN 978-84-9773-419-6 (Minerva. Revista de Filología Clásica, 2019)
Reseña de M. P. Leganés Moya y F. G. Hernández Muñoz, Demosthenis in Midiam, Universidad de León, 2008. 183 pp. ISBN 978-84-9773-419-6